Pengaruh Supervisi Kepala Sekolah dan Tingkat Pendapatan Terhadap Kinerja Guru di Sekolah Menengah Kejuruan di Kecamatan Lalan Kabupaten Musi Banyuasin - Antari, Ni Made Ita; Mahriadi, Nopriawan; Sandy, Amiruddin (@-Publik: Jurnal Administrasi Publik, 2026)
The principal is the center of leader who regulates and manages activities to be more directed, focused and has experienced significant improvements. Therefore, the principal plays a crucial role in improving the performance of teachers to be more enthusiastic and professional in teaching and developing themselves in transferring knowledge to students. With a very basic reason that the teacher has a very important role in determining the quality of the teaching that has been carried out. Teachers are needed to be able to play an active role as managers of the teaching and learning process, act as facilitators who always try to create class organization, use teaching methods as well as the attitudes and characteristics of teachers in managing the teaching and learning process. Productivity is influenced by many factors of income or income. Teachers at UPT SMK N 9 Musi Banyuasin have varying incomes. ASN teachers who are certified educators can be said to have enough income, because in addition to getting the basic salary of the ASN teachers, they also get a professional allowance equal to the basic salary they get. Meanwhile, ASN teachers who are not certified educators only get a basic salary. Meanwhile, honorary teachers only hope for BOS funds, which are very limited in number. The original purpose of this study was to find out how big the impact of principal supervision on teacher performance, to find out how big the effect of income level on teacher performance and to find out how big the impact of principal supervision and income level together on teacher performance in SMK in Lalan District, District Banyuasin Music. The research was conducted at UPT SMK N 9 Musi Banyuasin. The research population was 25 teachers of UPT SMK N 9 Musi Banyuasin using a saturated sample. The data collection technique is using a questionnaire/questionnaire. Data were analyzed by descriptive and inferential methods (multiple linear regression).